Mr. Magorium's Wonder Emporium [videorecording (DVD)] - Helm, Zach; Ludzik, Ted; Portman, Natalie, 1981-; Hoffman, Dustin, 1937- (20th Century Fox Home Entertainment, 2008)
Mr. Magorium owns the most amazing store in the world, where all the toys literally come to life. When the boss decides to retire, the shop throws a tantrum, and all its wonders begin to cease. Now Mr. Magorium's reluctant manager, skeptical accountant, and most loyal customer must work together to save the emporium by finding a little magic within themselves.